Partial Root-Zone Drying Technique: from Water Saving to the Improvement of a Fruit Quality - Jovanovic, Zorica; Stikic, Radmila (Frontiers in Sustainable Food Systems, 2018)
Due to climate changes and increased demands of different water users (agriculture, industry, domestic) water becomes scarce resources worldwide. Since irrigated agriculture is the one of the largest consumer of these resources (so called blue water footprint), irrigation management must be shifted from maximal production per crop area to maximal production per unit of water used by crops. Among the strategies for reducing water footprints, changing the full irrigation to the reduced crop’s water supply (deficit irrigation techniques) is one of the options. In this mini-review we present the latest advances of partial root-zone drying (PRD) applications in different agricultural plants, with the special emphases on the PRD effects on increasing WUE, yield and yield quality. We describe two PRD practical approaches (alternate and fixed), background of PRD induced increase in yield and water use efficiency and improved understanding about nutrient use efficiency. The evidence of PRD effect on the increase in nutritional and health attributes of yield in different species is also presented. Because of limited available data, further research is needed to understand complex biosynthetic pathway and synthesis of nutritive and healthy related metabolites and antioxidants in PRD treated plants. Practical application and promotion of this knowledge will allow farmers in water scarce areas to adapt PRD not only as a strategy for saving water, improving nutrient use and increase/sustain yield, but also for producing food with enhanced nutritive and health characteristics.